Successful management of a rare radius schwannoma mimicking malignant bone tumors: A case report and literature review - Sun, Nianzhe; Khan, Umar Zeb; Zeng, Lei; Wu, Panfeng; Xiong, Qin; Peng, Lushan; Yu, Hong; Tang, Juyu (Frontiers in Surgery, 2023)
Background: Schwannoma, a set of benign tumor originating from Schwann cells, generally occurs in the spinal cord and peripheral nerves. As a rare subset of schwannomas, intraosseous schwannomas, accounting for about 0.2%, impinges the mandible, sacrum, and spine as the decreased order. Furthermore, so far, only 3 cases of the radius intraosseous schwannoma have been reported in the PubMed search. therefore, the disease was treated differently and harvested different outcomes. Case presentation: A twenty-nine years old male patient who complained of painless mass on the radial side of right forearm was diagnosed with intraosseous schwannomas of radius from the radiograph, three-dimensional computed tomography reconstruction, magnetic resonance imaging, pathology, and immunohistochemistry. Due to the special profession of construction engineer, a different type surgery to reconstruct the radius graft defect using bone micro-repairing techniques was performed, harvesting a more reliable bone healing and more early function recovery. Meanwhile, there were no clinic and radiography findings to suggest any recurrence at the 12 months follow-up. Conclusions: To repair small segmental bone defects of radius caused by intraosseous schwannomas, vascularized bone flap transplantation combined with three-dimensional imaging reconstruction planning may yield better results. Keywords: Intraosseous schwannomas, Radius, Vascularized bone flap, Microreconstruction surgery, Bone tumor.